2016
DOI: 10.1016/j.ssmph.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Self-identified race, socially assigned skin tone, and adult physiological dysregulation: Assessing multiple dimensions of “race” in health disparities research

Abstract: Despite a general acceptance of “race” as a social, rather than biological construct in the social sciences, racial health disparities research has given less consideration to the dimensions of race that may be most important for shaping persistent disparities in adult physical health status. In this study, we incorporate the social constructionist view that race is multidimensional to evaluate the health significance of two measures of race, racial self-identification and the socially perceived skin tone of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 50 publications
(67 reference statements)
0
44
1
Order By: Relevance
“…While researchers have previously suggested feminine behaviors are linked to better health while masculine behaviors are linked to poorer health, Hart, Saperstein, Magliozzi, and Westbrook () demonstrated there may be a health penalty for cisgender individuals whose gender identities do not align with normative expectations of gender performance (men appearing more masculine and women appearing more feminine). Similarly, scholars have complicated dominant conceptualizations of race by examining skin tone in predicting subsequent health (Cobb, Thomas, Pirtle, & Darity, ; Cuevas, Dawson, & Williams, ; Monk, ). These findings push health scholars to complicate current measurements and conceptualizations of various identities, as many studies examining gender and racial differences in health conflate sex and gender and race and skin tone, respectively.…”
Section: Developments: Reconceptualizing Discrimination and Health Oumentioning
confidence: 99%
“…While researchers have previously suggested feminine behaviors are linked to better health while masculine behaviors are linked to poorer health, Hart, Saperstein, Magliozzi, and Westbrook () demonstrated there may be a health penalty for cisgender individuals whose gender identities do not align with normative expectations of gender performance (men appearing more masculine and women appearing more feminine). Similarly, scholars have complicated dominant conceptualizations of race by examining skin tone in predicting subsequent health (Cobb, Thomas, Pirtle, & Darity, ; Cuevas, Dawson, & Williams, ; Monk, ). These findings push health scholars to complicate current measurements and conceptualizations of various identities, as many studies examining gender and racial differences in health conflate sex and gender and race and skin tone, respectively.…”
Section: Developments: Reconceptualizing Discrimination and Health Oumentioning
confidence: 99%
“…Perceived appearance, one's own subjective evaluation of their appearance, was used to capture socially-assigned race in two studies [32,37]. In another study, the interviewer's rating of skin tone was used as a marker of socially-assigned race for its "generalized perception of other" [13]. Lopez et al uses a slightly different approach to measure sociallyassigned (i.e., ascribed) race by querying respondents about self-perceived race, socially-ascribed race and…”
Section: Measurement Of Socially-assigned Racementioning
confidence: 99%
“…Only one study used a biomarker of physical health. Cobb et al [13] investigated whether interviewer observed sociallyassigned race was associated with allostatic load, as an indicator of physiologic dysregulation [13]. In the Cobb et al [13] study, the strength of the association between self-identified versus socially-assigned race was relatively equal, with socially-assigned race showing a slightly higher estimate.…”
Section: Health Outcomes Self-rated Health and Physical Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Race, when assessed in this fashion, is typically based on skin color and often neglects the genetic ancestry. 11 Recent studies suggest there is substantial admixture and misclassification of race in the United States when based on self-reported skin color. 12 Genetic ancestry can be accurately determined using well-characterized ancestry informative germline markers.…”
Section: Introductionmentioning
confidence: 99%